2017
DOI: 10.1111/1462-2920.13956
|View full text |Cite
|
Sign up to set email alerts
|

Type VI secretion systems in plant‐associated bacteria

Abstract: SummaryThe type VI secretion system (T6SS) is a bacterial nanomachine used to inject effectors into prokaryotic or eukaryotic cells and is thus involved in both host manipulation and interbacterial competition. The T6SS is widespread among Gram‐negative bacteria, mostly within the Proteobacterium Phylum. This secretion system is commonly found in commensal and pathogenic plant‐associated bacteria. Phylogenetic analysis of phytobacterial T6SS clusters shows that they are distributed in the five main clades prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
200
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(208 citation statements)
references
References 82 publications
7
200
0
1
Order By: Relevance
“…Notably, a gene that encodes a type VI secretion protein (XC0699) also was identified in the ChIP‐seq data. The type VI secretion system (T6SS) is a bacterial molecular mechanism that injects toxic effectors into host cells and thus is involved in bacterial–host competition and interaction (Ho et al , ; Bernal et al , ). Like the T3SS, the T6SS also is widespread among gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a gene that encodes a type VI secretion protein (XC0699) also was identified in the ChIP‐seq data. The type VI secretion system (T6SS) is a bacterial molecular mechanism that injects toxic effectors into host cells and thus is involved in bacterial–host competition and interaction (Ho et al , ; Bernal et al , ). Like the T3SS, the T6SS also is widespread among gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…All five clades have been found in plant‐associated bacteria (Bernal et al ., ). Interestingly, Xanthomonas species carry different T6SS clusters from clades 3 and 4 (Boyer et al ., ; Bernal et al ., ). Phylogenetic analysis of Xanthomonas T6SS gene clusters based on tssB nucleotide sequence showed that clade 3 could be further subdivided into two subclades, the first comprising all T6SS associated with EcfK/PknS homologues, and the second all T6SS belonging to clade 3 that are not associated with EcfK/PknS homologues (Supporting Information Table S1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…T6SS gene clusters have been classified into four subtypes (T6SS i-iv ) (Boyer et al, 2009;Br€ oms et al, 2010;Russell et al, 2014;B€ ock et al, 2017), the majority belonging to T6SS i , which have been further subdivided into five phylogenetic clades (Boyer et al, 2009). All five clades have been found in plant-associated bacteria (Bernal et al, 2018). Interestingly, Xanthomonas species carry different T6SS clusters from clades 3 and 4 (Boyer et al, 2009;Bernal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Type VI secretion systems (T6SSs) are molecular nanoweapons used by Gram-negative bacteria to inject toxic proteins into eukaryote or bacterial cells (Cianfanelli et al, 2016a). T6SSs are ubiquitously found in plant-associated Pseudomonas (Barret et al, 2011;Bernal et al, 2018): the vast majority of Pseudomonas genomes sequenced to date possesses at least one T6SS cluster, and some strains possess up to four T6SS clusters (Marchi et al, 2013;Bernal et al, 2017). T6SSs are involved in interbacterial competition (Decoin et al, 2014;Bernal et al, 2018) and in disease-suppression (Marchi et al, 2013;Chen et al, 2016;Bernal et al, 2017).…”
Section: Traits Involved In Biocontrol Plant-growth Promotion and Rhmentioning
confidence: 99%
“…Collectively, the 63 strains under study harbour T6SS clusters from the six phylogenetic groups that are known to be present in Pseudomonas spp. (Barret et al, 2011;Bernal et al, 2018): groups 1.1 (H2-T6SS), 1.2, 2, 3 (H1-T6SS), 4A (H3-T6SS) and 4B ( Fig. 4 and Supporting Information Fig.…”
Section: Traits Involved In Biocontrol Plant-growth Promotion and Rhmentioning
confidence: 99%